Social Cohesion in Inclusive Community Development: A Case Study of Sumberagung Village, Ngantang District, Malang Regency - Firdausi, Faizah Ulumi; Fatmawati, Fatmawati; Agustin, Amanah (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
Inclusive development is development that provides equal opportunities for all members of society to participate and benefit from development without discrimination.This study aims to analyze the factors causing low social and economic inequality in Bendorejo Hamlet, Sumberagung Village, Ngantang District, Malang Regency. This phenomenon is interesting because the distribution of income in the hamlet tends to be even, in contrast to the general conditions in rural areas in Indonesia. The study used a qualitative approach with a case study, involving the Hamlet Head, community leaders, residents, and business groups. Data collection techniques included in-depth interviews, participatory observation, and documentation studies, analyzed using the Miles, Huberman, & Saldana model and tested through triangulation. The results show that low inequality is influenced by a culture of mutual cooperation, social solidarity, participatory leadership, and trust-based local economic management. The inclusive and participatory development model strengthens social justice. This research contributes to the academic literature and can be a practical reference for village governments and inspiration for other regions.